Review on the Scale-Up Methods for the Preparation of Solid Lipid Nanoparticles - Sakshi V. Khairnar; Pritha Pagare; Aditya Thakre; Aswathy Rajeevan Nambiar; Vijayabhaskarreddy Junnuthula; Manju Cheripelil Abraham; Praveen Kolimi; Dinesh Nyavanandi; Sathish Dyawanapelly (MDPI AG, 2022)
Solid lipid nanoparticles (SLNs) are an alternate carrier system to liposomes, polymeric nanoparticles, and inorganic carriers. SLNs have attracted increasing attention in recent years for delivering drugs, nucleic acids, proteins, peptides, nutraceuticals, and cosmetics. These nanocarriers have attracted industrial attention due to their ease of preparation, physicochemical stability, and scalability. These characteristics make SLNs attractive for manufacture on a large scale. Currently, several products with SLNs are in clinical trials, and there is a high possibility that SLN carriers will quickly increase their presence in the market. A large-scale manufacturing unit is required for commercial applications to prepare enough formulations for clinical studies. Furthermore, continuous processing is becoming more popular in the pharmaceutical sector to reduce product batch-to-batch differences. This review paper discusses some conventional methods and the rationale for large-scale production. It further covers recent progress in scale-up methods for the synthesis of SLNs, including high-pressure homogenization (HPH), hot melt extrusion coupled with HPH, microchannels, nanoprecipitation using static mixers, and microemulsion-based methods. These scale-up technologies enable the possibility of commercialization of SLNs. Furthermore, ongoing studies indicate that these technologies will eventually reach the pharmaceutical market.